2017
DOI: 10.1002/oby.22010
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effect of Lifestyle Interventions on Adipose Tissue Gene Expression: Implications for Carcinogenesis

Abstract: Objective: The mechanisms driving the associations between body weight and physical activity levels and multiple types of cancer are not yet well understood. The purpose of this review was to examine the effects of lifestyle interventions on proposed biomarkers of lifestyle and cancer risk at the level of adipose tissue in humans. Methods: Embase, MEDLINE, and CINAHL were searched by using keywords relating to exercise or diet interventions, adipose tissue biology, and outcomes of interest. Eligible studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
3
24
1
Order By: Relevance
“…Previous studies on exercise and adipokines have described minor effects, at least compared with different weight-loss regimes [20]. These observations are in agreement with our study, which revealed modest changes in mRNA levels (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies on exercise and adipokines have described minor effects, at least compared with different weight-loss regimes [20]. These observations are in agreement with our study, which revealed modest changes in mRNA levels (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas several scientists have described adipose tissue responses to different weight-loss regimens in a variety of human populations and animal models [15,24,35,52] is a lack of studies on the response to exercise, and especially in reporting results after a long-term period of exercise in humans [15,20,21]. One study applied microarrays on scWAT before and after 6 months of an exercise intervention in 14 postmenopausal women and found no apparent alterations in transcript levels [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…c and d ). These findings stand in stark contrast to the conclusions of a systematic review by Campbell et al . of 19 studies that evaluated gene expression in relation to weight loss and PA interventions in an effort to derive implications for carcinogenesis.…”
Section: Discussioncontrasting
confidence: 99%
“…23 Adiponectine is reduced by adipose tissue hypoxia and oxidative stress, 10 especially so in central fat distribution and increases in serum by weight loss. 24 Obese children also have lower serum adiponectin levels. 25 Hypertension is another established risk factor for RCC.…”
Section: Discussionmentioning
confidence: 99%